PENEGAKAN HUKUM BAGI PELAKU TINDAK PIDANA PENCURIAN DATA NASABAH PERBANKAN MENURUT UNDANG – UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - YUSUF, MOHAMAD (Universitas Nasional, 2022)
This research is focused on one of the criminal acts of cyber crime in thebanking sector, namely in the form of criminal acts of theft of banking customerdata. The act of stealing debit or credit card information by accessing automatedteller machines and illegally copying the information contained on the magneticstripe of the customer's (victim) debit or credit card to gain control over thecustomer's (victim) account.The purpose of this research is to analyze law enforcement for criminal actsof theft of banking customer data according to the law on information andelectronic transactions. And to analyze the punishment of the perpetrators of thecrime of theft of banking customer data according to the law on information andelectronic transactions. The research uses a normative juridical approach thatemphasizes library research. In this research, the legislation approach, conceptual approach, and case approach are used. Sources of legal materials used are primary, secondary and tertiary legal materials. The analysis of legal materials used is qualitative.Based on the results of the study, it shows that law enforcement used as thelegal basis for cybercrime cases is Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE). With the existence of the ITE Law, it is hoped that it can protect the information technology user community in Indonesia, this is important considering the number of internet technology users is increasing from year to year. The increasing use of the internet on the one hand provides a lot of convenience for humans in carrying out their activities, on the other hand it makes it easier for certain parties to commit a criminal act, this technological advance also affects the lifestyle and mindset of humans. information. The punishment carried out by law enforcement against the theft of customer data is based on existing laws and regulations such as Law no. 21 of 2011 Article 29 in the form of providing facilities for resolving customer complaints that have suffered losses which state that financial services business actors must be responsible for consumer (customer) losses.